Export of environmental goods: India's potential and constraints. (27th July 2015) - Nguyen, Van Son; Kalirajan, Kaliappa
Abstract: Using data from the period 1996–2010, this paper identifies the nature of constraints that make India, which is one of the emerging environmental goods and services (EGS) exporters, unable to realize its export potential of environmental goods (EG). The empirical results show that the growth of India's exports of EG was negatively affected by 'behind the border' constraints such as weak infrastructure and institutions, while the effect of 'explicit beyond the border' constraints such as partner countries' tariffs and exchange rates on the exports of EG was relatively small. The reduction of India's trading partners' 'implicit beyond the border' constraints such as weak infrastructure and institutions significantly contributed toward India's exports of EG, especially during the period 2005–2010.